Physical and electrochemical behaviors of AgX (X = S/I) in a GeS2–Sb2S3 chalcogenide-glass matrix. Issue 5 (1st April 2020) - Ma, Baochen; Jiao, Qing; Zhang, Yeting; Sun, Xing; Yin, Guoliang; Zhang, Xianghua; Ma, Hongli; Liu, Xueyun; Dai, Shixun
Abstract: Ion-conducting chalcogenide glasses of a Ag X ( X = S/I)-modified GeSbS system were triumphantly synthesized through the conventional techniques of melt quenching. The evolution of the physical and structural natures of these samples were examined through density and microhardness tests, DSC, and Raman scattering spectroscopy. The electric features of the bulk samples were studied by means of impedance spectroscopy. Room-temperature ionic conductivity dramatically increased by six orders of magnitude from 7.68× 10 −10 to 3.54 × 10 −4 S/cm with increasing Ag + content. The blocking effect, a novel phenomenon caused by the presence of a small amount of I ions in the glass system, was also observed, and its corresponding mechanism was proposed. The blocking effect hindered a portion of the mobile carriers in the network. Another phenomenon, i.e., the saturation of Ag ions, resulted in a slow increase in ionic conductivity at high Ag + dopant concentrations. These results provide novel insights into structural evolution and electrochemical properties of metal-doped solid electrolytes.